Cultural values in American and Spanish TV advertising at the beginning of COVID-19 pandemic (Communication & Society, 2021)
This article discusses the similarities and differences found in some Spanish and American television advertisements broadcast at the beginning of the COVID-19 pandemic. To carry out this study, forty advertisements shown on television in the two countries during the months of March and April 2020 were analysed. Qualitative and quantitative analysis considered the cultural dimensions of identity, uncertainty avoidance and masculinity. In addition, the Chi-square formula was also applied in order to confirm that the differences found in both groups of adverts were not significantly important. The results show that a great deal of similar messages and even expressions was conveyed to both audiences in both countries, although some differences were also found. Besides, the main goal of these ads in both groups was to comfort the audience, and not to clearly promote or advertise the product. Thus, this study demonstrates once again that despite the differences that these two cultural groups display, and which are usually portrayed in intercultural literature, the context highly influences the values typically assigned to a linguistic community. That is reflected in the discourse of speakers, and it is the reason why we can find values opposite to those expected in a cultural group.